A Carbon Accounting and Trading Platform for the uk Construction Industry - George Blumberg; Maurizio Sibilla (Energies, 2023)
Atmospheric carbon dioxide emanating from activities associated with the construction of buildings in the UK contributes approximately 16% of the uk’s total emissions and will need to be reduced significantly to meet international agreements. Against this scenario, this paper presents a novel perspective for carbon accounting and trading that proposes the use of a platform for the uk construction industry as a possible solution. This suggestion assumes that taxation should be synchronised with phases of the entire life cycle of the building and that tax credits (or deficits) should remain an asset of the building itself. In this regard, a strategy is in place in the uk, but with gaps in how it will be implemented. To resolve these gaps, firstly, this paper explores and integrates three socio-technical components (i.e., carbon accounting, trading, and certification) that form an essential set of tools required for the management of taxes directed at property developers and construction companies. Then, it points out the need for a suite of computer-based systems to facilitate the recording of emissions information, the purchase of carbon offsets, and a way to access specialist financial services. As a result, a trading platform is conceptualised that makes use of blockchain technology as a foundation for future research.